EARLY DETECTION FOR CHILD GROWTH AND DEVELOPMENT IN POSYANDU DADAPKUNING VILLAGE, CERME-GRESIK SUB-DISTRICT - Mira Triharini; Monica Octa Alfiana; Naurah Syafiqah Larasati; Sharfina Az-Zahrin Hakim; Puti Hanalya Rengganis (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2023)
Introduction: The incidence of stunting in the village of Dadapkuning Cerme-Gresik is currently 6 cases. Early detection is crucial for identifying and addressing growth and developmental issues promptly, thereby reducing the risk of stunting. The team of KKN-BBK Dadapkuning created a program to improve Integrated Services Post (Posyandu) by conducting Early Detection of Child Growth and Development (DDTK). Purpose of study is to early detect on developmental deviations in toddlers and pre-schoolers to early identification to promote the healthy development of children. Methods: The method used was a qualitative descriptive approach and data collection techniques were taken based on the results of observations on 20 toddlers and direct interviews with parents. This examination is carried out using a Developmental Pre Screening Questionnaire (KPSP) which contains several instructions to the child and several questions to be asked for parents or caregivers. Results: 2 children were obtained with a Doubtful interpretation of the results (M), because there was an answer "No" on the KPSP sheet, especially on social independence points. Conclusion: Early detection of the growth and development of toddlers is very important to identify deviations as early as possible and intervene appropriately. Health workers need to provide education to parents in providing optimal stimulation for children's growth and development. KEYWORDS community services; early detection; stunting.